An Analysis of Student Learning Challenges in Elementary School Science Subject - Agus Syahputra; Risma Delima Harahap; Islamiani Safitri (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The aim of this study is to analyze the many aspects of learning challenges that elementary school students encounter when learning science. The method of research was descriptive with a qualitative focus. All the students in classes IV, V, and VI were employed as research subjects. The researcher served as the instrument in this study, supplemented by interview, observation, and documentation criteria, while data analysis was accomplished through data reduction, presentation, and conclusion. As a result of the research, the largest degree of difficulty encountered by the students was with school facilities and infrastructure, at 96.73%, while the second highest level was with the learning media used by the teachers, at 82.45%. The next highest level was the indication of student interest in science lessons, which had a percentage value of 75%. This was because some students still did not comprehend how science was taught, as indicated by the lowest score of 73.90%. The existence of the challenges in science learning had a significant impact on student interest in learning and understanding level, resulting in a less effective teaching and learning process in the classroom. The solution to the above problems is for the teacher to obtain a better understanding of the students' needs while they are studying, for the teacher to employ a variety of learning media that entice students to learn, and for the principal to provide comprehensive facilities that support positive learning outcomes.